2012
DOI: 10.1016/j.humov.2012.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fatigue on synergies in a hierarchical system

Abstract: We investigated the effect of fatigue produced by timed maximal voluntary contraction (MVC) of the index finger of one of the hands on performance in MVC and accurate cyclic force production tasks in right-handed subjects. Based on earlier studies, we hypothesized that fatigue would produce an increase in the indices of force-stabilizing synergies in both hands as well as between the hands in two-hand tasks. Synergies were defined as co-varied adjustments of commands to fingers (modes) across cycles that stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 78 publications
(114 reference statements)
3
12
0
Order By: Relevance
“…We expected the adaptations to fatigue to be consistent with our previous studies where both V UCM and V ORT increased in accurate force production tasks during fatigue with V UCM showing a larger increase (Park et al, 2012; Singh, SKM, Zatsiorsky, & Latash, 2010a; Singh et al, 2010b; Singh et al, 2012). Therefore, our second hypothesis was that indices of force stabilizing synergies would increase at both levels of the hierarchy.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We expected the adaptations to fatigue to be consistent with our previous studies where both V UCM and V ORT increased in accurate force production tasks during fatigue with V UCM showing a larger increase (Park et al, 2012; Singh, SKM, Zatsiorsky, & Latash, 2010a; Singh et al, 2010b; Singh et al, 2012). Therefore, our second hypothesis was that indices of force stabilizing synergies would increase at both levels of the hierarchy.…”
Section: Discussionsupporting
confidence: 86%
“…Some studies have shown that in motor tasks that involve a redundant set of elements, the goal-relevant features of performance are relatively preserved during fatigue (Gates & Dingwell, 2008; Huffenus, Amarantini, & Forestier, 2006). We have also shown this to be true in accurate force production tasks (Park, Singh, Zatsiorsky, & Latash, 2012; Singh et al, 2010b; Singh, Zatsiorsky, & Latash, 2012). In the current study, we investigated the effects of exercise-induced fatigue of a single digit on motor variability and digit coordination in a static prehension task.…”
Section: Introductionsupporting
confidence: 53%
“…First, we did not explicitly test the effect of fatigue on the force production. However, the force levels observed in this study are lower than those required to produce measurable fatigue (Singh et al 2012). Second, we utilized a 5-s rest period during the discontinuous tasks.…”
Section: Concluding Commentsmentioning
confidence: 56%
“…Regarding the differences found according to the side tested (dominance), studies on motor units of voluntary muscles have identified lower average firing rates, lower recruitment thresholds, and greater firing rate/force delay in the dominant hand as compared to the non-dominant hand [19]. In addition, muscle synergies and predictive mechanisms of movement provide an advantage to the dominant side [20,21]. These findings can contribute to the better performance on the dominant side in our subjects.…”
Section: Discussionmentioning
confidence: 67%